Conversational Interfaces and the Challenges of Design and Development of Accessibility Requirements: A Report on Studies with the Older Public - Teles de Oliveira, Cynthya Letícia; Padilha Modesto de Araújo, Lucas; Rios da Hora Rodrigues, Kamila; Garcia Manzato, Marcelo (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Older adults often face difficulties using digital systems, sometimes depending on others for tasks or abandoning technology. In chatbot scenarios, these challenges relate to platform limitations, developers’ prior knowledge, and users’ skills. This study examines conversational systems from empirical research with older adults. Methodology: Chatbots were developed following accessibility guidelines and evaluated through tests with older participants. Findings: The results indicate the need to rethink software implementation and study approaches, paying attention to unreported participant attitudes. The insights obtained were key to refining the guidelines and advancing more accessible chatbot solutions for older users.